Cost-effectiveness of edoxaban compared to warfarin for the treatment and secondary prevention of venous thromboembolism in the UK. Issue 1 (1st January 2018) - Clay, Emilie; Jamotte, Aurélien; Verhamme, Peter; Cohen, Alexander T.; Van Hout, Ben. A.; Gumbs, Pearl.
ABSTRACT: Background : Venous thromboembolism (VTE), which includes pulmonary embolism (PE) and deep vein thrombosis (DVT), is the third most common acute cardiovascular disease and represents an important burden for patients and payers. Objective : The aim was to estimate the cost-effectiveness of edoxaban, a non-VKA oral anticoagulant vs. warfarin, the currently most prescribed treatment for VTE in the UK. Study design : A Markov model was built using data from the Hokusai-VTE randomised controlled trial to estimate the lifetime costs and quality-adjusted life years (QALYs) in patients with VTE treated with edoxaban or warfarin over a lifetime horizon, from the UK National Health Services perspective. The model included VTE recurrences, VTE-related complications (post-thrombotic syndrome and chronic thromboembolic pulmonary hypertension), and several types of bleeds associated with anticoagulation treatment. Patients were treated during a period of 6 months after the first VTE event, followed by flexible treatment duration (from 6 months to lifetime) after recurrence, i.e., tertiary prevention. Results : Edoxaban was found dominant vs. warfarin with 0.033 additional QALY and £55 less costs. The reduction of patient management costs, specifically monitoring costs, outweighed the higher drug costs. Edoxaban was dominant in all subgroups (index DVT only, all PE cases (PE with or without DVT), PE without DVT and PE with DVT). Cost-savings ranged from £54 to £81 while additional QALYs ranged from 0.031 to 0.046. Edoxaban was found dominant in 88.6% of cases and cost-effective in additional 10.9% of cases considering a £20, 000 threshold in the probabilistic sensitivity analysis. Conclusion : Edoxaban may improve patients' quality of life in a lifetime horizon without additional costs for the healthcare system due to lower bleeding risk and no monitoring cost compared to warfarin.